2019
DOI: 10.1099/acmi.0.000037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening of the human parvoviruses B19 and bocavirus 1 in the study of congenital diseases as applied to symptomatic pregnant women and children

Abstract: Introduction B19 virus (B19V) and bocavirus 1 (HBoV1) are human pathogenic parvoviruses that are prevalent worldwide and are responsible for a diverse and not yet fully established spectrum of clinical manifestations. Objective To screen B19V and HBoV1 in patients with clinical manifestations associated with acquisition of the infection during gestation. Methods A retrospective, observational study was performed that included serum samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Importantly, it has been demonstrated that during surges, secondary attack rates are significant [28], as has been demonstrated by our data as well. Rates have also been shown to be highly dependent on occupation deriving substantial exposure opportunities, such as daycare center workers or schoolteachers, among whom infection rates of susceptible women can climb to 20 to 30 percent [28], while hydrops fetalis and fetal death have also been demonstrated to rise during outbreaks [25,41]. Increased rates in this population could also be related to secondary transmission in households, a hypothesis that should be researched in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it has been demonstrated that during surges, secondary attack rates are significant [28], as has been demonstrated by our data as well. Rates have also been shown to be highly dependent on occupation deriving substantial exposure opportunities, such as daycare center workers or schoolteachers, among whom infection rates of susceptible women can climb to 20 to 30 percent [28], while hydrops fetalis and fetal death have also been demonstrated to rise during outbreaks [25,41]. Increased rates in this population could also be related to secondary transmission in households, a hypothesis that should be researched in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lifetime prevalence of B19V is relatively high throughout the world; where genotypes 1 is prevalent worldwide, genotype 2 is rare and currently considered ancestral to genotype 1, while genotype 3 can be found primarily in Africa and South America; the intergenotype genetic divergence is up to 13% [25,26]. Prevalence increases with age and varies across geographic locations, with school age seroprevalence of 20-60% and up to 80% in adults in Western countries [27].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts were stored at −20 °C for later use in subsequent end-point PCR assays for detection of HBoV1, targeting a 354 bp sequence of the NP1 gene as performed previously [3, 22, 23]⁠. PCR products were visualized in 8.5 % polyacrylamide gels stained with silver solution (0.11 M AgNO 3 ) [24]⁠.…”
Section: Methodsmentioning
confidence: 99%
“…Штаммы с последовательностями, идентичными прототипным штаммам В19, Au и Wi, составляют генотип 1. К генотипу 2 относятся изоляты HaAM и K71 (прототипы А6 и LaLi), а к 3 генотипу -изоляты штаммов V9 и D91.1 [33,95]. В соответствии с различиями нуклеотидных последовательностей геномов геновиды подразделяются на штаммы 1А, 1В, 2А, 3А и 3В.…”
Section: парвовирусная инфекция в19vunclassified